Istoriograficeskij analiz razvitija rossijskogo futbola v sovremennoj Rossii - Alexeev, V. N. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
The author investigated various aspects of the development of the Russian football, described in the domestic and foreign literature.